Anti-Corruption Education Urgence for State Islamic Religious Teachers - Ahmad Asrin (Budapest International Research and Critics University, 2021)
The aims of this study to find out anti-corruption education urgence for state Islamic religious teachers. This study use Qualitative Research Methods. The result show that Corruption is seen as an extra ordinary crime, therefore it requires extraordinary efforts to eradicate it. Efforts to eradicate corruption which consists of two major parts, namely prosecution and prevention will never be optimally successful if only carried out by the government without involving public participation. Therefore it is not an exaggeration if students - as an important part of society who are the inheritors of the future - are expected to be actively involved in efforts to eradicate corruption in Indonesia. Of course, these efforts are still a discourse and the benefits will not be felt in the short term, but in the long term this discourse is believed to be fruitful. If higher education starts, especially PTKIN, it will inspire others, and one day it comes to efforts to draft a legal product with anti-corruption nuances that can be initiated in PTKIN, such as the Bill, Ranperda and the like. Hopefully PTKIN can play a more significant role in the future. Thus, corruption can be minimized and even eliminated from this beloved country, including through optimizing the role of PTKIN.